El sonido [ç] chileno: ¿una articulación conservadora o innovadora? (Estudios de Fonética Experimental)
This paper pretends to be a unifying response to the lack of connection between the synchronic and diachronic approaches based on the [ç] allophone of /x/ in South American Spanish. Two experiments were carried out: an acoustic analysis based on laboratory, semi-directed and spontaneous speech, and a perception experiment (AB discrimination task including spontaneous speech segments as well as German and Bulgarian sounds). The results obtained revealed an articulatory and historical explanation according to the evolutionary patterns of Spanish. Specifically, a parallel emerged between the assimilation by co-articulation of [t͡ʃ] and [ç], characterized by the evolution of a non-palatal sound with another neighboring palatal sound.